2002
DOI: 10.1128/mcb.22.11.3729-3743.2002
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CBP-Mediated Protein Acetylation by the Ets Family Oncoprotein PU.1

Abstract: Aberrant expression of PU.1 inhibits erythroid cell differentiation and contributes to the formation of murine erythroleukemias (MEL). The molecular mechanism by which this occurs is poorly understood. Here we show that PU.1 specifically and efficiently inhibits CBP-mediated acetylation of several nuclear proteins, including the hematopoietic transcription factors GATA-1, NF-E2, and erythroid Krüppel-like factor. In addition, PU.1 blocks acetylation of histones and interferes with acetylation-dependent transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 90 publications
3
66
0
1
Order By: Relevance
“…Consistent with the second model, CBP directly acetylates the GATA1 protein, which increases its transcriptional activity (31,32). In addition, a recent study suggested that the Pu.1 protein blocks erythroid differentiation by blocking the CBP-HAT-catalyzed acetylation of GATA1 and other proteins (33).…”
supporting
confidence: 49%
“…Consistent with the second model, CBP directly acetylates the GATA1 protein, which increases its transcriptional activity (31,32). In addition, a recent study suggested that the Pu.1 protein blocks erythroid differentiation by blocking the CBP-HAT-catalyzed acetylation of GATA1 and other proteins (33).…”
supporting
confidence: 49%
“…(GATA) inhibits the function of GATA (PU.1), resulting in dominion by itself, during the development from hematopoietic stem cells toward the monocyte (erythrocyte/megakaryocyte) lineage (21)(22)(23)(24)(25)(26)(27)(28). In contrast, PU.1 and GATA1/GATA2 exhibit a cooperative function in mast cells, as follows: 1) PU.1 and GATA2 cooperatively induce mast cell development (20); 2) PU.1 and GATA1 synergistically transactivate cell type-specific gene regulation in mast cells (5,29); and 3) PU.1 is required for GATA1 expression in mast cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Spi-1/PU.1 and the major erythroid transcription factor GATA-1 cross antagonize one another through direct interaction (Rekhtman et al, 1999;Zhang et al, 1999Zhang et al, , 2000Nerlov et al, 2000). On the other hand, Spi-1/PU.1 inhibits CBP-mediated acetylation of erythroid transcription factors GATA-1, EKLF and NF-E2 (Hong et al, 2002). Both inhibitory effects of Spi-1/PU.1 are thought to contribute to erythroid differentiation arrest and to malignant transformation.…”
Section: Splicing Of Exon 16 In Differentiating Mel Cells Is Regulatementioning
confidence: 99%